2019
DOI: 10.1177/0956247819866124
|View full text |Cite
|
Sign up to set email alerts
|

Does urbanization make emergence of zoonosis more likely? Evidence, myths and gaps

Abstract: Rapid urbanization in the global South is adding epidemiological and nutritional challenges and increasing disease and health burdens for citizens. Greater movement of people, animals, food and trade often provides favourable grounds for the emergence of infectious diseases, including zoonoses. We conduct a rapid evidence scan to explore what is known and hypothesized about the links between urbanization and zoonosis emergence. This points to rapid demographic growth, migration and density, increased movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
69
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 82 publications
(38 reference statements)
0
69
0
1
Order By: Relevance
“…[30,31]. Rickettsia-positive eas parasitizing R. rattus in these three areas indicate that this species could play a key role in spreading the disease from wild to urban environments [16,32]. Conversely, we also observed that wild species enter human-occupied environments since they provide shelter and food.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[30,31]. Rickettsia-positive eas parasitizing R. rattus in these three areas indicate that this species could play a key role in spreading the disease from wild to urban environments [16,32]. Conversely, we also observed that wild species enter human-occupied environments since they provide shelter and food.…”
Section: Discussionmentioning
confidence: 80%
“…This species has been described to have a "random walk" type of dispersal behavior, so it can easily go from wild to domestic environments [33]. These ndings are important because these rodent species could act as "bridge hosts" and aid in the spread of the disease [32,34]. On the other hand, in natural areas, the rodent species most frequently captured was A. hirta; this, like A. olivacea, had a high prevalence of Rickettsia-positive eas.…”
Section: Discussionmentioning
confidence: 99%
“…This rodent was mainly captured in urban areas; however, we also found it in rural and natural areas, this occurs mainly because these rodents have an omnivore diet and plasticity in their behavior, characteristics that allow them to inhabit a great diversity of environments, adapting successfully to urban, rural and wild environments [30,31]. Rickettsia-positive eas parasitizing R. rattus in these three areas indicate that this species could play a key role in spreading the disease from wild to urban environments [16,32]. Conversely, we also observed that wild species enter humanoccupied environments since they provide shelter and food.…”
Section: Discussionmentioning
confidence: 96%
“…This species has been described to have a "random walk" type of dispersal behavior, so it can easily go from wild to domestic environments [33]. These ndings are important because these rodent species could act as "bridge hosts" and aid in the spread of the disease [32,34]. On the other hand, in natural areas, the rodent species most frequently captured was A. hirta; this species, like A. olivacea, had a high prevalence of Rickettsia-positive eas.…”
Section: Discussionmentioning
confidence: 99%
“…This species has been described to have a "random walk" type of dispersal behavior, so it can easily go from wild to domestic environments [33]. These ndings are important because these rodent species could act as "bridge hosts" and aid in the spread of the disease [32,34]. On the other hand, in natural areas, the rodent species most frequently captured was A. hirta; this, like A. olivacea, had a high prevalence of Rickettsia-positive eas.…”
Section: Discussionmentioning
confidence: 99%